1992
DOI: 10.1007/bf00845357
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and physiological predictors of lipids in black males

Abstract: The association between lipids and both psychological and physiological measures were examined in this study of healthy black males. The results revealed that certain psychological measures, namely, State and Trait Curiosity and Trait Anger, explained a significant proportion of the variance in high-density lipoproteins (HDL), low-density lipoproteins (LDL), and triglycerides. Although psychological factors accounted for a significant proportion of the variance in lipids (29% for HDL, 25% for LDL, 64% for LDL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…However, anger proneness has been associated with CHD risk factors, including hyperlipidemia and hypertension. 30,31 Recently, it has also emerged as a risk factor for the development of CHD. 32,33 In the same ARIC data set, normotensive individuals with high anger proneness were at a 2.2-fold greater risk for CHD than those with a low level of anger.…”
Section: Discussionmentioning
confidence: 99%
“…However, anger proneness has been associated with CHD risk factors, including hyperlipidemia and hypertension. 30,31 Recently, it has also emerged as a risk factor for the development of CHD. 32,33 In the same ARIC data set, normotensive individuals with high anger proneness were at a 2.2-fold greater risk for CHD than those with a low level of anger.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson et al, 7 in cross-sectional analyses, showed that trait anger was positively associated with the LDL/HDL ratio and triglyceride levels. Durel et al 8 reported a positive association between trait anger and blood pressure (systolic and diastolic) and between trait anger and cardiovascular reactivity.…”
mentioning
confidence: 99%
“…The highest contributions for reducing stress are exercise, income and balanced diet as per primary data. It is to be noted that there is no multicollinearity among the independent variables since the range of VIF are from the result from higher level of stress including blood pressure, hypertension [7,8], self-reported illness [9], immune function, diabetes, hyperglycemia [10], heart disease [11], dyslipidemia [12], preterm birth [13] and increased carotid artery intima-media thickness [14]. In addition, health damaging behaviours such as drug misuse [15] and cigarette smoking [16] have also been found to bear strong correlation with stress.…”
Section: Discussionmentioning
confidence: 99%